2013
DOI: 10.1002/ett.2632
|View full text |Cite
|
Sign up to set email alerts
|

Radio‐frequency energy harvesting potential: a stochastic analysis

Abstract: This paper considers the energy harvesting potential from ambient electromagnetic waves in the radio frequency (RF) communications spectrum. Because of chaotic positioning nature of cells, handsets and hotspots, the analysis employs stochastic geometry theory to derive the mean and probability distribution of the received RF radiation energy available for harvesting. The mean and density function of energy harvested, as a function of transmitter deployment density, spectrum and pathloss characteristics are giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Leveraging the spatial distributions of RF transmitters found in the previous subsection, research in [6] found that the received power density P rx is linearly proportional to the bandwidth B and the transmit power density P tx , and has a complex monotonic relationship with the distance-dependent pathloss exponent α and the node density Λ. Given that the energy from each transmitter will vary significantly depending on whether the propagation is largely Line-of-Sight (LoS, α = 2) or Non-LOS (NLoS, α > 2), one can consider a dual-slope approach (as shown in Fig.…”
Section: ) Upper-bound (Full Spectrum Utilization) With Dualslope Pamentioning
confidence: 97%
See 1 more Smart Citation
“…Leveraging the spatial distributions of RF transmitters found in the previous subsection, research in [6] found that the received power density P rx is linearly proportional to the bandwidth B and the transmit power density P tx , and has a complex monotonic relationship with the distance-dependent pathloss exponent α and the node density Λ. Given that the energy from each transmitter will vary significantly depending on whether the propagation is largely Line-of-Sight (LoS, α = 2) or Non-LOS (NLoS, α > 2), one can consider a dual-slope approach (as shown in Fig.…”
Section: ) Upper-bound (Full Spectrum Utilization) With Dualslope Pamentioning
confidence: 97%
“…For example, there is a strong body of evidence that macro-BSs are distributed following a Poisson point process (PPP), i.e., each macro-BS is deployed independently to others. In the literature, the probability density function (pdf) of the distance r between the energy harvesting device at an arbitrary location and the n-th nearest macro-BS is given by [6] f BS,Rn (r; n, Λ). Fig.…”
Section: A Statistical Modeling: Distance Distributionsmentioning
confidence: 99%
“…This module would take advantage of the available environmental energy (photovoltaic energy, RF energy, mechanical vibrations, etc. ), collecting and storing it for future use [24][25][26]. In this regard, different strategies have been followed to integrate a harvester module in RFID tags.…”
Section: Introductionmentioning
confidence: 99%
“…As the main novelty, a DC-DC buck converter is used instead of a charge pump [24][25][26] or linear regulator [25,29] as other authors have previously done. The DC-DC controller circuit used in the present work is aimed to energise ultra-low power (below mW) applications.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only two works study the impact of EMR energy harvesting in large scale networks [8], [9]. Both works consider direct communication scenarios and give useful insights on the potential benefits of the EMR EH technology.…”
Section: Introductionmentioning
confidence: 99%